Cultural Preservation in a Globalized World: Strategies for Sustaining Heritage - Abrar Hiswara; Adit Mohammad Aziz; Yenik Pujowati (Westscience Press, 2023)
Cultural preservation in the face of globalization is a pressing concern for diverse societies worldwide. This research delves into the complexities of sustaining cultural heritage in the rich and diverse landscape of Indonesian culture, a nation with a mosaic of traditions, languages, arts, and customs. Employing a mixed-methods approach that combines qualitative and quantitative research methods, including interviews, surveys, and content analysis, this study identifies the challenges and strategies associated with cultural preservation in Indonesia. The qualitative findings reveal that rapid modernization, urbanization, media influence, cultural displacement, commodification, and appropriation pose significant challenges to the preservation of Indonesia's cultural heritage. These challenges resonate with global discussions on the impact of globalization on cultural diversity. Furthermore, qualitative data highlight the importance of strategies such as cultural education, documentation and archiving, community involvement, and supportive policy and legislation. Quantitative survey data reinforce these qualitative insights, indicating a strong desire among respondents for cultural education, documentation, community involvement, and policy support. The majority of respondents expressed awareness of their cultural heritage and active participation in cultural activities. The implications of this research extend beyond Indonesia, as the findings provide valuable insights into the broader discourse on cultural preservation in a globalizing world. The strategies identified in this study offer potential solutions for preserving cultural heritage in diverse regions facing similar challenges. Ultimately, this research underscores the significance of safeguarding cultural diversity amidst the currents of globalization.